2023
DOI: 10.1002/pan3.10529
|View full text |Cite
|
Sign up to set email alerts
|

How do different types and characteristics of green space impact mental health? A scoping review

F. Beute,
M. R. Marselle,
A. Olszewska‐Guizzo
et al.

Abstract: Green space matters for mental health but is under constant pressure in an increasingly urbanising world. Often there is little space available in cities for green areas, so it is vital to optimise the design and usage of these available green spaces. To achieve this, experts in planning, design and nature conservation need to know which types and characteristics of green spaces are most beneficial for residents' mental health. A scoping review of studies that compare different green space types and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 286 publications
0
9
0
Order By: Relevance
“…While we recorded comparisons to other NbS types, further synthesis was hindered by the use of multiple heterogeneous NbS comparators without specifying outcomes for each, as also noted by Dick et al (2020). A recent review provided a possible approach to generalize the comparative results by focusing on specific pairs of NbS types, such as forest and park (Beute et al, 2023). Their results were mixed due to heterogeneity in NbS characteristics and research design.…”
Section: Discussionmentioning
confidence: 99%
“…While we recorded comparisons to other NbS types, further synthesis was hindered by the use of multiple heterogeneous NbS comparators without specifying outcomes for each, as also noted by Dick et al (2020). A recent review provided a possible approach to generalize the comparative results by focusing on specific pairs of NbS types, such as forest and park (Beute et al, 2023). Their results were mixed due to heterogeneity in NbS characteristics and research design.…”
Section: Discussionmentioning
confidence: 99%
“…O' Brien and Forster (2023), in an evaluation of the Active Forests Programme, found that one of the ways in which people valued being recreationally active in a forest environment was because of the beauty and variety of those landscapes. The health and well-being benefits of treescapes have also been highlighted in many studies (Beute et al, 2020;Tyrväinen et al, 2019), although further research is needed to understand more about the characteristics of treescapes that have the most impact on health. Spiritual, symbolic and sensory values related to forests have been identified as being important to a diverse range of people (Church et al, 2014;Cloke & Jones, 2002;Kenter et al, 2014;O'Brien et al, 2012.…”
Section: Treescape Values and The Importance Of Sandc Valuesmentioning
confidence: 99%
“…However, a distinction needs to be made between exposure to and active participation in green spaces, also referred to as experiencing green spaces [16]. These experiential aspects of participation in green spaces may be very relevant to their health effects, yet they have been studied less often, as a recent scoping review on the mental health impacts of various green space types and characteristics concludes [27]. To the best of our knowledge, there are no systematic reviews of the effects of participation in the creation of urban green spaces on health.…”
Section: Of 26mentioning
confidence: 99%